2006
DOI: 10.1063/1.2162695
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement effect in ZnO∕Mg0.2Zn0.8O multishell nanorod heterostructures

Abstract: We report on photoluminescence measurements of Mg0.2Zn0.8O∕ZnO∕Mg0.2Zn0.8O multishell layers on ZnO core nanorods. Dominant excitonic emissions in the photoluminescence spectra show a blueshift depending on the ZnO shell layer thickness attributed to the quantum confinement effect in the nanorod heterostructure radial direction. Furthermore, near-field scanning optical microscopy clearly shows sharp photoluminescence peaks from the individual nanorod quantum structures, corresponding to subband levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…3, the I ZnO ͑QW͒ peak position did not depend on the QB layer thickness of the coaxial nanorod quantum structures. This result was also clearly confirmed from PL spectra for thicker QB layer thicknesses of 12 and 78 nm, 8 indicating that the PL blueshift in the coaxial nanorod quantum structures results from a quantum confinement effect rather than the composition intermixing.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…3, the I ZnO ͑QW͒ peak position did not depend on the QB layer thickness of the coaxial nanorod quantum structures. This result was also clearly confirmed from PL spectra for thicker QB layer thicknesses of 12 and 78 nm, 8 indicating that the PL blueshift in the coaxial nanorod quantum structures results from a quantum confinement effect rather than the composition intermixing.…”
supporting
confidence: 52%
“…4,[6][7][8] These nanorod quantum structures exhibit a blueshift in the band edge PL peak due to a quantum confinement effect in ZnO well layers between the ZnMgO barrier layers. 4,[6][7][8][9] Meanwhile, several studies have reported on coaxial nanorod heterostructures including Ge/ Si, Si/ CdSe, and GaP / GaN. 1,10,11 However, quantum effects in coaxial nanorod quantum structures have rarely been reported, 7,8 and quantum confinement effect in the coaxial nanorod quantum structures has not thoroughly been studied.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, embedding quantum structures in a single nanorod can confine both carriers and emitted photons efficiently in the nanorod as well as can tune the wavelength of emitted light. [6][7][8][9] Despite the successful fabrications of the nanorod heterostructures, nanodevice applications of the nanorod heterostructures have rarely been reported. Only a few studies have been reported about the use of the heterostructures as components of light emitting nanodevices and high electron mobility nanotransistors 7,10 and the practical use of the nanodevices has still remained out of reach.…”
mentioning
confidence: 99%